2019
DOI: 10.1021/acs.inorgchem.9b01719
|View full text |Cite
|
Sign up to set email alerts
|

Coligand Effects on the Field-Induced Double Slow Magnetic Relaxation in Six-Coordinate Cobalt(II) Single-Ion Magnets (SIMs) with Positive Magnetic Anisotropy

Abstract: Two mononuclear cobalt­(II) compounds of formula [Co­(dmphen)2(OOCPh)]­ClO4·1/2H2O·1/2CH3OH (1) and [Co­(dmbipy)2(OOCPh)]­ClO4 (2) (dmphen = 2,9-dimethyl-1,10-phenanthroline, dmbipy = 6,6′-dimethyl-2,2′-bipyridine and HOOCPh = benzoic acid) are prepared and magnetostructurally investigated. Each cobalt­(II) ion is six-coordinate with a distorted octahedral CoN4O2 environment. The complex cations are interlinked leading to supramolecular chains (1) and pairs (2) that grow along the crystallographic c-axis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 89 publications
2
31
0
Order By: Relevance
“…These FIRMS/HFEPR results are quite similar to those obtained for other cobalt(II) complexes with a distorted octahedral CoN 4 O 2 environment. 38 It is worth mentioning that the obtained D value is very close to that obtained from dc magnetic measurements of 68 cm −1 . The FIRMS spectra also reveal another magnetic transition at 793 cm −1 , which corresponds to the excited Kramers doublet next to the S = 3/2 level.…”
Section: Firms/hfeprsupporting
confidence: 82%
See 1 more Smart Citation
“…These FIRMS/HFEPR results are quite similar to those obtained for other cobalt(II) complexes with a distorted octahedral CoN 4 O 2 environment. 38 It is worth mentioning that the obtained D value is very close to that obtained from dc magnetic measurements of 68 cm −1 . The FIRMS spectra also reveal another magnetic transition at 793 cm −1 , which corresponds to the excited Kramers doublet next to the S = 3/2 level.…”
Section: Firms/hfeprsupporting
confidence: 82%
“…Recent theoretical calculations of the lowest energy vibrational modes for two field-induced distorted octahedral Co(II) SIMs have demonstrated that their energies are close to the experimental thermal energy barriers for Orbach relaxation mechanisms. 38 This fact led to a suggestion that the thermal energy barrier is tied to the lowest vibrational modes of the metal complex, so when these vibrational modes are thermally populated, the magnetization reversal becomes faster, promoting the elimination of the magnetization blocking. Moreover, it has been suggested that the direct relaxation between two quasi-degenerate ground states is accelerated in structurally flexible SMMs.…”
Section: Compoundmentioning
confidence: 99%
“…The values for the pre-exponential factor and activation energy are consistent with those of the other Co( ii ) complexes showing this behavior. 34–36…”
Section: Resultsmentioning
confidence: 99%
“…[73][74][75][76] The observed behavior and anisotropic values are similar to other published mononuclear Co(II) complexes in pseudo-octahedral geometry and also in other Co(II) CPs. [77][78][79][80][81][82] Dynamic susceptibility measurements were performed to study the possibility of slow relaxation of the magnetization. Without an applied static dc eld, no c 0 signal was observed; however, when an external dc eld was used, a dependence of c 0 appeared.…”
Section: Magnetic Propertiesmentioning
confidence: 99%